Burnout in the Pharmaceutical Activity: The Impact of COVID-19 - Santos, Pedro Machado dos; Silva, Claudia Ribeiro da; Costa, Diana; Torre, Carla (Frontiers in Psychiatry, 2022)
Pharmacists are one of the healthcare groups who were involved in the response to the pandemic COVID-19, maintaining an essential service to the population. The study aimed to assess the occurrence of pharmacist’s burnout, and determine outcomes for each of its dimensions; to identify potential characteristics associated with principal outcomes; and to determine profiles and critical limits for the burnout dimensions. The statistical analysis yielded profiles based on the normalized (z) values for the 3 dimensions of the MBI. Logistic regression was performed to identify the risk factors associated with burnout, and (ii) χ2 test was used to compare the categorical variables training in the COVID-19 area with the confidence in caring for patients with this disease. From a total of 1362 pharmacists that participated in the study, 91.4% were involved in direct patient care activity and 7.7% in non-direct patient care activity. Concern for the future (76.8%), workload (72.7%), and patient volume (62.2%) were the main influencing factors on work-related feelings. This new profile-based approach provides an understanding of the burnout experience and distinct relationships with various work-life factors and suggests that each profile reflects a different work-life crisis that would require a unique intervention strategy. Pharmacists who had been trained in COVID-19 were the most confident and showed a higher efficacy/outcome rate. Workload appears only as a predictor of high EE, with great impact on those who worked during the 3-month period more than 50 hours per week and on those who worked almost every weekend. The latter with greater predictive power of high EE (p≤0,001). Our data indicate that pharmacists who have been involved in direct care activities are at the highest risk of burnout. However, they were able to avoid depersonalisation and cynicism and thereby burnout syndrome.